KEPASTIAN HUKUM PERKAWINAN ANTAR AGAMA DALAM PERSPEKTIF HAK ASASI MANUSIA - Erwinsyahbana, Tengku; Ramlan, Ramlan (Borneo Law Review Journal, 2017)
The dominance of religious influence in the field of marriage law is inevitable, for marriage is also a worship that the Lord commands the human race. The religious rules governing marriage can not be ruled out by anyone who wants to carry out their marriage, but there is a tendency that religious values or precepts are neglected, on the grounds of human rights, whereas based on the 1945 Constitution and Law no. 39 of 1999, that in certain cases the exercise of human rights can be limited by religious values. Given that interfaith marriages are forbidden by religion (Islam), then interfaith marriage on the grounds of human rights, can not be justified. An important paradigm that also needs to be straightened out that marriage is not included as a human right, because it is the right to form a family that includes human rights, the way it is done through legitimate marriages, that is legitimate according to religion and state law